Disaster Management on Small Islands; Lessons from Flash Flood Disaster in Rua Village, Ternate Island, Indonesia - Mohammad Ridwan Lessy; Nani Nagu; Kalpin Nur (Jurnal Ilmu Lingkungan, 2025)
Small islands have been identified as regions that exhibit susceptibility to natural disasters and the impacts of climate change. This arises from a multitude of constraints, such as limited size, geographical isolation, high population density, closeness to the ocean, and reliance on natural resources. The recurrent flash flood calamities on Ternate Island underscore the deficiencies in disaster management strategies for smaller islands. It is imperative to enhance disaster management on small islands, particularly in light of the anticipated escalation in the severity of disasters in the future. This study examines the underlying factors contributing to the flash floods in Rua Village, Ternate Island, as well as assessing the effectiveness of disaster management strategies implemented on Ternate Island. Through the application of both qualitative and quantitative research methodologies, we meticulously examined the gathered data and represented it in a thematic map. The findings of the study indicated that elements such as precipitation, topography, and river dynamics, along with the properties of rock composition, soil stability, and soil movement characteristics, contribute to the occurrence of flash floods in Rua Village. Moreover, inadequate disaster management challenges all stakeholders in Ternate who are striving to establish a resilient society to disasters.